A Special class of Hypersurfaces parametrized by lines of curvature in R4 - C. Riveros, Carlos M. (2018)
In this paper we study hypersurfaces in R4 parametrized by lines of curvature with three distinct principal curvatures and with Laplace invariants mji = mki = 0; mjik 6= 0 for i; j; k distinct fixed indices. We characterize locally a generic family of such hypersurfaces in terms of the principal curvatures and three vector valued functions of one variable, this family includes a classe of Dupin hypersurfaces. Moreover, weshow that these vector valued functions are invariant under inversions and homotheties.